2020
DOI: 10.1097/md.0000000000021840
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of preoperative prognostic nutritional index in ovarian cancer

Abstract: Background: The prognostic significance of preoperative prognostic nutritional index (PNI) in ovarian cancer (OC) is uncertain, and this study is aimed to clarify the prognostic significance. Methods: We used 4 common databases for conducting a systematic review and meta-analysis, and eligible studies were included in the analysis. The association of preoperative PNI with overall survival (OS), progression-free survival (PFS), and clinicopathological parameters was anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 26 publications
2
22
0
Order By: Relevance
“…For OC, the pooled HR for OS and PFS was 1.28 (0.73-2.26) and 1.82 (1.41-2.36), respectively. These findings were validated by a recently published metaanalysis (45). For CC, the pooled HR for OS and PFS was 2.96 (1.87-4.70) and 2.54 (1.41-4.58), respectively.…”
Section: Gynecological Cancerssupporting
confidence: 66%
“…For OC, the pooled HR for OS and PFS was 1.28 (0.73-2.26) and 1.82 (1.41-2.36), respectively. These findings were validated by a recently published metaanalysis (45). For CC, the pooled HR for OS and PFS was 2.96 (1.87-4.70) and 2.54 (1.41-4.58), respectively.…”
Section: Gynecological Cancerssupporting
confidence: 66%
“…The mechanism by which a low nutritional status decreases the survival time of breast cancer patients is still not sufficiently understood. The PNI, as a systemic immune–nutrition index based on the peripheral lymphocyte count and serum albumin levels, represents the immune and nutritional status and is also a significant biomarker for many tumors ( Dai et al, 2020 ; Hao et al, 2020 ; Zhang et al, 2020 ). The PNI was initially developed to evaluate the postoperative complications in patients who received gastrointestinal surgery ( Onodera et al, 1984 ).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous inflammatory biomarkers, such as neutrophils, lymphocytes, platelets and so on, had been implied as the prognostic predictor for different cancers. 21–23 In osteosarcoma, some researchers revealed that lymphocyte-to-monocyte ratio (LMR) was positively related to overall and event-free survival rates of patients, while the neutrophil-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR) showed the opposite trends. 24–26 Several studies also implied that nonsteroidal anti-inflammatory drugs (NSAIDs) could inhibit the progression of osteosarcoma.…”
Section: Discussionmentioning
confidence: 99%